THE USE OF PICTURES IN TEACHING WRITINGDESCRIPTIVE TEXT A Quasi -Experimental Study in Junior High School in Bandung - Dina Wahyu Fitriana, - (2013)
This study aimed to investigate the effectiveness of pictures in teaching descriptive text. It examined how pictures could influence students' descriptive writing skill and their perceptions towards the learning. This study was conducted from the consideration that writing skill is difficult to acquire. A quasi-experimental design was used in this study and the data were collected though pretest. posttest, and questionnaire to gain relevant data. The data were analyzed quantitatively using t-test SPSS version 21 for Windows, while the questionnaire was analyzed qualitatively. In selecting the samples, seventh grade students of a junior high school in Bandung were selected. There were two classes as the samples; the first was experimental group and the other was the control group. From the result of the study, it was shown that pictures are effective in improving students' descriptive text writing skill. It is indicated by the results of t-test computation, the significant value of the posttest score was 0.002 < 0.05 (two-tailed), Furthermore, the effectiveness was also supported by the students' responses in the questionnaire. Most of the students felt that through pictures their writing skills improved. The improvements were in terms of vocabularies, comprehension and ideas.